The self and psychotherapy: are the predictions ACT makes about self-as-content accurate? - Naidoo, Rohan James (2011)
Objectives: The evidence base for Acceptance and Commitment Therapy’s (ACT) overall effectiveness is highly promising. However, the extent to which the six processes comprising ACT have been investigated is extremely variable. In particular, the process regarding the self and therapeutic change is in need of validation, having never been subjected to empirical investigation The objective of the present study was to achieve this by testing whether the predictions ACT makes regarding the self and therapeutic change are supported by quantitative data. The specific prediction to be tested were that a) those with a fixed sense of self and low psychological flexibility will display high therapeutic resistance and b) those with a fluid sense of self and high psychological flexibility will display a strong tendency towards value-based behaviour.